Cesarska epifania. Ernst H. Kantorowicz jako badacz bizantyńskiej teologii politycznej - Pawlik, Robert (Vox Patrum, 2021)
Ernst Hartwig Kantorowicz is not well known as a Byzantinist, nevertheless he has dedicated a great deal of his scholarly attention to the Byzantine East. In the 1940’s, while teaching at Berkeley University, he regularly attended conferences with lectures on Eastern topics. In1950’s, he inaugurated his lifelong collaboration with the Byzantine centre at Dumbarton Oaks. In the last years of his life, he worked on a book project which was to collect his works on byzantine political theology. The book was conceived as a „sequel” to the „King's Two Bodies”, the culmination of his research on medieval political theology in the Western world. Death prevented him from the completion of the Byzantine project, but unpublished conference lectures as well as three studies published in the journal „Dubarton Oaks Papers” allow us some insight into the Kantorowicz’s vision. In the present paper I try to reconstruct Kantorowicz’s contribution to the study of political theology, or rather „political Christology” of the Byzantine Empire.